Clinical evaluation of three urine screening tests. - Murray, P R (1987)
Evaluations of screening tests for bacteriuria have traditionally compared the test results with those of quantitative urine cultures. However, many patients with symptomatic urinary tract infections can have less than 10(5) CFU/ml in their urine. Therefore, the results of urine culture and three screening tests (Bac-T-Screen, Chemstrip LN [which tests for leukocyte esterase and nitrate reductase], and Gram stain) were correlated with the clinical classification of urinary tract infection. The Bac-T-Screen test detected 98, 93, and 100% of the infections classified as probable, possible, and asymptomatic, respectively. In contrast, the Gram stain, leukocyte esterase, and nitrate reductase tests were all insensitive screening tests for infection. Additionally, only 45% of the patients with probable infections had greater than or equal to 10(5) CFU/ml. Thus, the majority of infected patients would not have been detected if quantitative urine cultures were used alone.